Perception of Traditional Public Transportation Service in Sub-Urban Area: Case Study Angkutan Kota Pondok Gede - Cililitan Route - Asep Wardiana; Susanti Handayani (Fakultas Teknik Sipil dan Perencanaan, 2023)
Expansion in the global economic sector has caused urbanization in many countries, including Indonesia. The fast-paced and widespread dynamics of urban society are one of the reasons for the development of the transportation system. However, Indonesia is facing a traffic jam problem, especially in Greater Jakarta. One of the main causes is people commuting from Bogor, Depok, Tangerang, and Bekasi to Jakarta to carry out various activities. Public transport is an important alternative to overcome people's dependence on private transportation. In this study, an assessment of the performance of public transport services for the Pondok Gede - Cililitan route was carried out based on user preferences. The method used is a quantitative approach to public transport passengers from Pondok Gede - Cililitan. The research parameters were conducted through the trip's characteristics and service quality. Based on the research, public satisfaction with Pondok Gede-Cililitan public transportation is easy to reach and change modes. On the other hand, the points of comfort, security, waiting time, speed, travel time, and regularity still need to be improved for the quality of service. As a form of management commitment, the results of this research can be used as material for evaluating the quality of public transport performance to re-optimize and increase public interest in using public transportation, especially public transport, to reduce regional congestion levels.